Trends and perceptions of evidence-based software engineering research in Malaysia - Salleh, Norsaremah; Nordin, Azlin (IEEE, 2015)
Evidence-based research has been matured and established in many other disciplines such as in Medicine and Psychology. One of the methods that has been widely used to support evidence-based practices is the Systematic Literature Review (SLR) method. The SLR is a review method that aims to provide unbiased or fair evaluation to existing research evidence. The aim of this study is to gather the trends of evidence-based software engineering (SE) research in Malaysia in particular to identify the usage of SLR method among researchers, academics or practitioners. Based on our tertiary study, we found only 19 published work utilizing evidence-based practices in Malaysia within SE and Computer Science related domains. We have also conducted a survey during SLR workshops for the purpose of gathering perceptions on using SLR. The survey was participated by 78 academics and researchers from five universities in Malaysia. Our findings show that researchers in this country are still at preliminary stage in practicing evidence-based approach. We believe that knowledge and skill on using SLR should be promoted to encourage more researchers to apply it in their research.